2023
DOI: 10.1101/2023.09.04.23294493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety and immunogenicity of VLPCOV-02, a SARS-CoV-2 self-amplifying RNA vaccine with a modified base, 5-methylcytosine, in healthy individuals

Masayuki Aboshi,
Kenta Matsuda,
Daisuke Kawakami
et al.

Abstract: Continuing emergence of variants of concern resulting in reduced SARS-CoV-2 vaccine efficacy necessitates additional prevention strategies. The structure of VLPCOV-01, a lipid nanoparticle-encapsulated, self-amplifying RNA COVID-19 vaccine with a comparable immune response to BNT162b2, was revised by incorporating a modified base, 5-methylcytosine to reduce reactogenicity, and an updated receptor-binding domain derived from Brazil (gamma) variant. Interim analyses of a phase 1 dose-escalation booster vaccinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Importantly, our phase I trial of saRNA-based SARS-CoV-2 vaccines has shown that they are safe and effectively elicit prolonged humoral immune responses against S RBD 14 . Furthermore, this study and another clinical trial have demonstrated that an saRNA-based vaccine with 5mC induces attenuated IFN-I responses in vitro and reduced systemic reactogenicity when injected to human, resulting in better safety profile 15 . This saRNA-based vaccine platform, particularly with modified RNA bases, will be useful to develop vaccines with long-lasting effectiveness and reduced reactogenicity against not only SARS-CoV-2 but also other pathogens.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Importantly, our phase I trial of saRNA-based SARS-CoV-2 vaccines has shown that they are safe and effectively elicit prolonged humoral immune responses against S RBD 14 . Furthermore, this study and another clinical trial have demonstrated that an saRNA-based vaccine with 5mC induces attenuated IFN-I responses in vitro and reduced systemic reactogenicity when injected to human, resulting in better safety profile 15 . This saRNA-based vaccine platform, particularly with modified RNA bases, will be useful to develop vaccines with long-lasting effectiveness and reduced reactogenicity against not only SARS-CoV-2 but also other pathogens.…”
Section: Discussionmentioning
confidence: 67%
“…Interestingly, m5C incorporation into saRNA attenuates IFN-I and proinflammatory responses in PBMCs mainly due to the limited activation of the IFN-I pathway in pDCs. Although further reactogenicity studies of saRNA-m5C in animal models are currently in progress, we have already observed attenuated systemic reactions such as fevers in a human clinical trial conducted with saRNA-m5C vaccines 15 . While we were preparing this manuscript, a preprint by McGee and colleagues has also shown that cytosine modification enables saRNA to show enhanced and prolonged antigen expression and attenuated IFN-I responses 39 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations